Analisis Biaya Lingkungan PT Pupuk Sriwidjaja Palembang - Mutiara Kemala Ratu; Vhika Meiriasari (Jurnal Ilmiah Ekonomi Global Masa Kini, 2021)
Environmental costs incurred from the company's activities in order to maintain the environment is one form of information on environmental management accounting. With the use of environmental management accounting, companies can make efficiency and improve service quality in a sustainable manner. In addition, the environmental costs incurred on each product can be calculated accurately so that the calculation of the cost of the product can be more realistic and humane. However, in it’s implementation there are still many companies that have not been able to disclose it so that mostly of the cost was hidden in overhead costs which would then make it biased and unclear allocation. This research was conducted to determine the implementation of environmental costs from PT PUSRI Palembang as the object. PT PUSRI Palembang which has a close relationship with the community environment in its corporate activities is indeed an interesting object in this research. The results showed that PT PUSRI doesn’t have an external failure costs which presage that the company is good enough to prevent waste produced discharge to the environment. By comparing the environmental costs incurred from the years 2012-2014 showed percentage reduction of environmental costs toward operating costs, which is 0.01% annually. With the information provided in the environmental costs report it aimed to be able to help financial statements users (investors, management, creditors) in company’s decision making policies and programs related to environmental preservation in the future.Keywords: Enfironmental Cost, Waste, Company